1993
DOI: 10.1177/106002809302700408
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity Associated with Cisplatin Chemotherapy

Abstract: This patient may have experienced cisplatin-induced liver damage. Metoclopramide and ondansetron may have contributed to this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 11 publications
6
32
0
Order By: Relevance
“…In our study, this model also permitted the assessment of whether MI and CY cause any interactions and/or reduce tumor development. Many chemotherapeutic agents and drug combinations are very toxic to patients; for example, doxorubicin-associated cardiotoxicity (Mackay et al 1994), the hepatotoxicity of cisplatin (Cavalli et al 1978;Cersosimo 1993;Pollera et al 1987) and the neurotoxicity of paclitaxel (Postma et al 1995). In this study, we verified that MI-treated mice did not display any reductions in body weight or show any other clinical manifestations of MI-induced toxicity, such as hair loss (Crounse et al 1962).…”
Section: Discussionsupporting
confidence: 61%
“…In our study, this model also permitted the assessment of whether MI and CY cause any interactions and/or reduce tumor development. Many chemotherapeutic agents and drug combinations are very toxic to patients; for example, doxorubicin-associated cardiotoxicity (Mackay et al 1994), the hepatotoxicity of cisplatin (Cavalli et al 1978;Cersosimo 1993;Pollera et al 1987) and the neurotoxicity of paclitaxel (Postma et al 1995). In this study, we verified that MI-treated mice did not display any reductions in body weight or show any other clinical manifestations of MI-induced toxicity, such as hair loss (Crounse et al 1962).…”
Section: Discussionsupporting
confidence: 61%
“…The DLT of acute hepatotoxicity occurred at dose level 150 mg; the patient presented the toxicity at the end of chemotherapy treatment when she was also taking erythromycin and antiemetics. Acute severe hepatitis, though rare, is occasionally observed with EGFR inhibitors gefitinib or erlotinib (33), cisplatin (34), and erythromycin (35). All medications were interrupted and the patient presented complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The nephrotoxicity and ototoxicity of cisplatin are the most common dose-limiting factors in cancer chemotherapy (47). Cisplatin hepatotoxicity rarely occurs at standard doses, but it is frequently seen after administration of highdose cisplatin and can alter the clinical situation of patients (3). Previous studies showed that elevated cytochrome P450 2E1 (CYP2E1) levels can enhance cisplatin-induced hepatotoxicity (36), and metallothionein (MT)-knockout mice are more sensitive to cisplatin hepatotoxicity (35).…”
mentioning
confidence: 99%